ANALYSIS OF HEALTHCARE SERVICE QUALITY IN GOVERNMENT HOSPITALS USING CLUSTERING METHODS - Tuhfah, Riesa Aliya; Novareza, Oyong; Andriani, Debrina Puspita (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2025)
Hospitals play a crucial role in delivering healthcare services, directly influencing public health and overall well-being. Evaluating service quality is essential for enhancing patient satisfaction, as healthcare institutions must meet patient expectations to ensure effective service delivery. This study assesses hospital service quality using the Servqual model and clustering techniques to analyze patient perceptions. The Servqual framework evaluates five dimensions: tangibility, reliability, responsiveness, assurance, and empathy. A structured questionnaire was used to gather patient responses, utilizing a Likert scale to measure expectations and perceptions. Clustering techniques, including K-Means and Fuzzy C-Means, were applied to segment patient perception data, revealing four service quality categories: